The Corinth That Saint Paul Saw - Murphy-O'Connor, J. (The Biblical archaeologist, 1984)
Corinth in the first century A.D. was a wide-open boomtown at the crossroads of the ancient world. Based on historical texts and extensive excavations conducted at the site, this article recreates the city that was so important to the Pauline mission.